2013
DOI: 10.1097/pep.0b013e3182888495
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Training Following Orthopedic Surgery in Lower Limbs of Children With Cerebral Palsy

Abstract: Treadmill training during physical therapy is beneficial for children with CP who undergo orthopedic surgery in the lower limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 21 publications
0
33
0
3
Order By: Relevance
“…However, there was wide variation in effect size. Supporting studies also found evidence for improved endurance as a result of gait training, with only one case study reporting a decrease in distance covered after intervention . Retention of improved endurance was variable, with improvements both persisting and regressing …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there was wide variation in effect size. Supporting studies also found evidence for improved endurance as a result of gait training, with only one case study reporting a decrease in distance covered after intervention . Retention of improved endurance was variable, with improvements both persisting and regressing …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the within‐group effect size for each gait outcome reported, and pooled effect of treatment type: physical therapy and strength training; OGT; PBWSTT; treadmill training; gait training enhanced with virtual reality and feedback; and miscellaneous. The miscellaneous studies could not be considered to fit into other groups because of their diverse nature, including studies investigating backward walking, OGT with PBWS, treadmill training with transcranial direct current stimulation, treadmill training with ankle load, and treadmill training after surgery . While interpretation of results of this meta‐analysis should be treated with caution, a tendency towards increased effect size of gait training on walking speed can be observed in gait training groups with gait training enhanced with virtual reality and feedback.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations